Conceptual Design and Analysis of Four Types of Variable Stiffness Actuators Based on Spring Pretension. (21st May 2015) - Guo, Jishu; Tian, Guohui
The variable stiffness actuator (VSA) is an open research field. This paper introduces the conceptual design and analysis of four types of novel variable stiffness actuators (VSAs). The main novelty of this paper is focused on the convenience control of the torque and stiffness of the actuator. We do not need to design complicated control strategies to achieve the desired actuating torque and output stiffness. This feature is beneficial for real-time control. In order to achieve this advantage, three types of approximate quadratic springs and four types of stiffness regulation mechanisms are presented. For the first VSA, the relationship between the output stiffness and angular deflection is close to linear, and the fitted quadratic spring is easy to implement and compact. For the second VSA, the output stiffness is only related to the working radius, and the relationship between the exerted torque and angular deflection is linear. For the third VSA, two equivalent quadratic torsion springs are used. Compared with the existing quadratic torsion springs, the design method is simple and the structure size is compact. The stiffness and torque is a linear function of the kinematic parameters of the VSA. The novelty of the fourth VSA is the use of the tension spring set. The approximate quadratic tension spring is compact and easy to implement. The relationship between the output stiffness and the angular deflection is fairly linear. The conceptual layouts and working principles are elaborated for the four actuators. The characteristics of torque and stiffness of the VSAs are presented, and the mechanical solutions are illustrated.